2018
DOI: 10.3390/catal8050208
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linked Enzyme Aggregates of Feruloyl Esterase Preparations from Thermothelomyces thermophila and Talaromyces wortmannii

Abstract: Cross-linked enzyme aggregates (CLEA ®) technology is a well-established method in the current literature for the low-cost and effective immobilization of several enzymes. The main advantage of this particular method is the simplicity of the process, since it consists of only two steps. However, CLEA immobilization must be carefully designed for each desired enzyme, since the optimum conditions for enzymes can vary significantly, according to their physicochemical properties. In the present study, an investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The loss of enzyme activity after each cycle has been linked to the leaching of the enzyme or mechanical stress during centrifugation causing the CLEA pellet to clump [36]. Our SEM images showed that CLEA-elastase exhibits a type 2 aggregate and this coheres with studies suggesting that type 2 aggregates are often formed by hydrophilic enzymes [45]. The DLS analysis provided insight into the diameter size of the aggregate in aqueous media, where the diameter of CLEA-elastase appeared to be significantly larger than that of a free elastase.…”
Section: Discussionmentioning
confidence: 56%
“…The loss of enzyme activity after each cycle has been linked to the leaching of the enzyme or mechanical stress during centrifugation causing the CLEA pellet to clump [36]. Our SEM images showed that CLEA-elastase exhibits a type 2 aggregate and this coheres with studies suggesting that type 2 aggregates are often formed by hydrophilic enzymes [45]. The DLS analysis provided insight into the diameter size of the aggregate in aqueous media, where the diameter of CLEA-elastase appeared to be significantly larger than that of a free elastase.…”
Section: Discussionmentioning
confidence: 56%
“…Among the various immobilization methods described in the literature, crosslinked enzyme aggregates (CLEAs) technology is one of the most prominent [ 20 ]. Many different enzymes have been immobilized in CLEA form, among them esterases [ 21 ], lipases [ 22 ], cellulases [ 23 ], and xylanases [ 24 ], which were used for various bioconversion applications, such as the production of cosmeceuticals [ 21 ], nutraceuticals [ 24 ], or even biofuels [ 22 ]. The advantages of CLEA technology include the simplicity of the method, the low overall cost of the procedure, and the fact that there is no need for solid support or dedicated specialized equipment.…”
Section: Introductionmentioning
confidence: 99%
“…The morphology of CLEAs depends on enzyme type, precipitant agent and the microenvironment of the enzyme when cross-linking (Zerva et al 2018 ). SEM micrographies revealed the formation of clusters with irregular, cluster shapes and low porosity for CALB-CLEAs (Fig.…”
Section: Resultsmentioning
confidence: 99%